Atmospheric controls on the annual cycle of North African dust - Engelstaedter, S; Washington, R (American Geophysical Union, 2007)
Dust emitted from desert regions and transported in the atmosphere has been recognized for its potential to alter the Earth's climate and environments. Satellite data show that the largest source regions of dust (i.e., hot spots) are located in dry, nonvegetated areas of West Africa and central Chad. Dust emissions from these sources follow a distinct seasonal cycle. Whereas our understanding of processes controlling the dust cycle of the Chad dust source has been improved through recent studies, our understanding of the West African sources is limited because of the remoteness of the sources and lack of surface observations. Using a satellite-derived dust index and reanalysis atmospheric fields, we show that the annual dust cycle at the West African dust hot spots is not related to changes in mean surface wind strength but it linked to small-scale high-wind events. We find that the annual dust cycle correlates well with changes in near-surface convergence associated with the annual north-south movement of the Inter-Tropical Convergence Zone (ITCZ). Dust emissions in West Africa are highest in June coinciding with the crossing of the convergence zone on its northward bound over the dust hot spots. The increase in convergence leads to enhanced surface gustiness suggesting that dry convection associated with an increase in the occurrence of small-scale high-wind events and vertical velocity are the main processes controlling the annual dust cycle at the West African dust sources.